PERLINDUNGAN HUKUM BAGI PENUMPANG PADA ANGKUTAN UMUM - Soekarno, Dwi Teguh; Astutik, Sri; Subekti, Subekti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This normative legal research analyzes the legal protection afforded to public transport passengers in Indonesia. Grounded in the concept of a rule-of-law state (Rechtsstaat), as stipulated in Article 1 Paragraph (3) of the 1945 Constitution, this study examines the existing legal framework—specifically Law No. 22 of 2009 on Road Traffic and Transportation and Law No. 8 of 1999 on Consumer Protection—to understand how passenger rights are guaranteed constitutionally and implemented sectorally. Using a normative legal research approach with a focus on doctrinal analysis of legislation, the study finds that passenger legal protection originates from the legal relationship created by a carriage agreement. This relationship establishes mutual rights and obligations, with the carrier held responsible for the passenger’s safety and comfort, often under the principle of strict liability. Various forms of legal protection, such as mandatory insurance schemes, dispute resolution mechanisms, and prohibitions against unfair standard clauses, serve to balance the unequal bargaining power between carriers and passengers. The research concludes that legal protection for passengers is an essential pillar for ensuring safety and justice within the transportation ecosystem. As technology advances, this protection will continue to evolve to accommodate new challenges posed by autonomous vehicles and Mobility as a Service (MaaS) systems. Therefore, it is recommended that regulations be updated proactively, law enforcement strengthened, and public education promoted to ensure that passenger rights remain protected in the future